KREATIFITAS GURU PAI DALAM MENUMBUHKAN MINAT BELAJAR SISWA DI SMK BAITUSSALAM LAMONGAN - Muslih, Imam; Khulailiyah, Ahsanatul; Muslim, Fathul (ILJ: Islamic Learning Journal, 2024)
Creatifity is an important thing for teachers in delivering ongoing learning materials, because then a teacher will certainly more easily understand the condition of students and the condition of the class when learning takes place. This study aims to determine the creativity used by Islamic Religious Education (PAI) teachers in fostering student interest in learning. High learning interest is an important factor in the success of learning, especially in PAI subjects at SMK Baitussalam Bluluk. This research used a qualitative approach with descriptive method. Data were collected through classroom observation, interviews with PAI teachers and document analysis related to learning strategies. The results showed that there are some effective creativity used by PAI teachers, namely developing new ideas in learning both using media and with various strategies. Student learning interest is very important, because with learning interest, the lerning process at SMK Baitussalam Bluluk can take place optimally. Student learning interest can increase if a teacher has his own creativity by combining various kinds of learning models that vary when learning takes place.